2012
DOI: 10.1111/aogs.12030
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing perinatal mortality in placental abruption

Abstract: Although mortality associated with placental abruption decreased during the study period, placental abruption still remains an important cause of perinatal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 17 publications
1
42
2
3
Order By: Relevance
“…However, a large scale review in the United States in 2001 reported that the high perinatal mortality with abruption was mainly due to its strong association with preterm delivery [17]. But with the advancement of obstetric service, the perinatal mortality has been reported as decreasing [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a large scale review in the United States in 2001 reported that the high perinatal mortality with abruption was mainly due to its strong association with preterm delivery [17]. But with the advancement of obstetric service, the perinatal mortality has been reported as decreasing [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data underscores that placental abruption has a profound impact on adverse outcomes surrounding the perinatal period. 6,14,46,47 Results from this multi-centre, prospective cohort study suggest that abruption is associated with a two-fold increased risk of abnormal psychomotor and mental deficits at 8 months, and a 1.7-fold increased risk of low IQ (<70) at 4 years. However, abruption does not appear to affect childhood IQ at 7 years.…”
Section: Resultsmentioning
confidence: 91%
“…3 Newborns of pregnancies complicated by abruption experience perinatal and infant mortality rates that are over 10-fold higher than those born after non-abruption pregnancies. [4][5][6] Among surviving infants, the risks of preterm delivery and growth restriction are also higher among abruption than non-abruption births. Despite these disproportionately high risks of adverse perinatal outcomes associated with abruption, the true public health significance and long-term sequelae of abruption remain are virtually unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a larger study protocol (1,(17)(18)(19). There were 7805 women with at least one placental abruption; some of these women had a recurrent abruption.…”
Section: Methodsmentioning
confidence: 99%